Urgensi Kepemimpinan Kristen di Era Society 5.0 - Topayung, Semuel Linggi (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2022)
Abstract: At this time, all aspects of each individual's life will be supported by technology. Industrial revolution 4.0 is not over yet, now Society 5.0 has arrived. This shows that the changing times, and the development of culture, is a reality that the church must face. How the role of church leaders in dealing with these challenges is highlighted. To answer this, the author uses a descriptive qualitative approach that is seen from the existing phenomena, either directly or through other literature. The role of leaders in providing spiritual guidance is so very important, church leaders must return to their functions to preach, teach, and serve as a form of love for God and fellow human beings. Church leaders must realize that the use of technology in church services is not necessarily accepted by all circles. All the conveniences presented in technology media have an impact on the growth of the congregation. Christian leaders must set an example for the congregation by being an example in their lives, and providing spiritual and social guidance. Abstrak: Pada masa ini, seluruh sendi kehidupan setiap individu hendak disokong oleh teknologi. Belum usai Revolusi industri 4.0, kini telah hadir Society 5.0. Hal tersebut menunjukkan, bahwa perubahan zaman, perkembangan budaya, merupakan suatu kenyataan yang harus dihadapi gereja. Bagaimana peran pemimpin gereja menghadapi tantangan tersebut begitu sangat disorot. Untuk menjawab hal tersebut, penulis menggunakan pendekatan kualitatif deskriptif yang dilihat dari fenomena yang ada, baik secara langsung ataupun melalui literatur lainnya. Peran pemimpin dalam memberikan pembinaan kerohanian begitu sangat penting, pemimpin gereja mesti mengembalikan kepada fungsinya untuk memberitakan, mengajarkan, dan melayani sebagai bentuk kasihnya kepada Tuhan dan sesama manusia. Pemimpin gereja mesti menyadari bahwa, penggunaan teknologi dalam layanan gereja tidak serta-merta diterima semua kalangan. Semua kemudahan yang tersaji dalam media teknologi, berdampak juga kepada pertumbuhan jemaat. Pemimpin Kristen mesti memberikan keteladanan kepada jemaat dengan menjadi contoh dari kehidupannya, memberikan bimbingan rohani, dan juga sosial.